Development of the WHO Antenatal Care Recommendations Adaptation Toolkit: a standardised approach for countries - Maria Barreix; Theresa A. Lawrie; Nancy Kidula; Fatim Tall; Maurice Bucagu; Ram Chahar; Özge Tunçalp (BMC, 2020)
Abstract Background Increasingly, WHO recommendations are defined by context-specific factors and WHO is developing strategies to ensure that recommendations are successfully adapted and implemented at country level. This manuscript describes the development of a toolkit to support governments to adapt the WHO recommendations on antenatal care (ANC) for a positive pregnancy experience for their context in a systematic manner. Methods The toolkit was developed in three steps. It was created with input from methodologists and regional implementation experts (Step 1) followed by a user-testing phase (Step 2), implemented during country stakeholder meetings. User testing consisted of stakeholder interviews that were transcribed, and data was categorised according to the content analysis method. Suggestions for toolkit improvement and issues identified during the interviews were assessed as serious, moderately serious or minor/cosmetic. Results A total of 22 stakeholders - comprising five Ministry of Health (MoH) consultants, four MoH policy-makers, and 13 advisors/implementers - from Burkina Faso, India, Rwanda and Zambia participated in user-testing interviews during stakeholder meetings held in each country between August 2018 and February 2019. Most stakeholders had a medical or nursing background and half were women. Overall, responses to the toolkit were positive, with all stakeholders finding it useful and desirable. User testing interviews highlighted four serious, four moderately serious and five minor/cosmetic issues to be managed. These were addressed in the final step (Step 3), an updated version of the WHO ANC Recommendations Adaptation Toolkit, comprised of two main components - a baseline assessment tool with spreadsheets for data entry and a Slidedoc®, a dual-purpose document for reading and presentation, outlining the qualitative data that shaped the women-centred perspective of the guidelines, accompanied by an instruction manual detailing the components' use. Conclusions The WHO ANC Recommendations Adaptation Toolkit was developed to support countries to systematically adapt the WHO ANC recommendations for country contexts. Using this approach, similar tools can be developed to support guideline implementation across different health domains and the continuum of care.